2015
DOI: 10.1002/ana.24508
|View full text |Cite
|
Sign up to set email alerts
|

Tracking sensory system atrophy and outcome prediction in spinal cord injury

Abstract: ObjectiveIn patients with subacute spinal cord injury (SCI), the motor system undergoes progressive structural changes rostral to the lesion, which are associated with motor outcome. The extent to which the sensory system is affected and how this relates to sensory outcome are uncertain.MethodsChanges in the sensory system were prospectively followed by applying a comprehensive magnetic resonance imaging (MRI) protocol to 14 patients with subacute traumatic SCI at baseline, 2 months, 6 months, and 12 months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 71 publications
2
117
0
Order By: Relevance
“…This indicates a correlation between the MT saturation and the transfer term, and, thus, the macromolecular fraction. The sensitivity of the MPM‐based MT saturation metric to myelination has been demonstrated in neuroscientific [Callaghan et al, ; Dick et al, ; Sereno et al, ] and clinical research studies [Freund et al, ; Grabher et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…This indicates a correlation between the MT saturation and the transfer term, and, thus, the macromolecular fraction. The sensitivity of the MPM‐based MT saturation metric to myelination has been demonstrated in neuroscientific [Callaghan et al, ; Dick et al, ; Sereno et al, ] and clinical research studies [Freund et al, ; Grabher et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…In summary, neurodegeneration in CSM, although different in causation, disease onset and progression trajectory, 3 resembles the pathophysiological processes of antero-and retrograde degeneration observed after spinal cord injury. 38,46,47 …”
Section: Journal Of Neurotraumamentioning
confidence: 99%
“…Investigations applying qMRI restricted to a set of regions-of-interest reported progressive volume loss in the internal capsule of SCI patients paralleled by myelin reduction at 12 months post-injury compared to baseline (Freund et al, 2013). Using the same technique in the very same cohort, the authors observed also myelin reduction in thalamus, cerebellum and brainstem in the same period of time (Freund et al, 2013;Grabher et al, 2015). These combined morphometry and tissue property findings in the early injury phase contrast with the absence of volume differences when comparing sub-acute (duration <1 year) and chronic (duration >1 year) patients with complete motor SCI (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…One of the well-established methods -voxel-based morphometry (VBM), was used to monitor local grey matter volume changes following SCI to deliver conflicting results ranging from lack of SCI related brain anatomy changes (Crawley et al, 2004) to evidence about profound sensorimotor cortex reorganization (Jurkiewicz et al, 2006;Wrigley et al, 2009a;Henderson et al, 2011;Freund et al, 2013). More recent reports demonstrate grey matter loss in nonmotor areas including anterior cingulate gyrus, insula, orbitofrontal gyrus, prefrontal cortex and thalamus (Wrigley et al, 2009b;Grabher et al, 2015;Chen et al, 2017). One of the potential reasons for the reported controversial findings is the fact that these studies pooled together patients with incomplete and complete SCI (Crawley et al, 2004;Jurkiewicz et al, 2006;Chen et al, 2017) not taking into account potential impact of differences in the time span since injury (Grabher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation